A comparative study of the primary rule for doubt from the viewpoint of Mohaghegh NÄÄ«nÄ« and ShahÄ«d Sadr - Ã˜Â¹Ã™Â„Ã›ÂŒ Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã›ÂŒ, Ã˜Â·Ã˜Â§Ã™Â‡Ã˜Â±; Ã˜Â²Ã˜Â±ÃšÂ¯Ã™ÂˆÃ˜Â´ Ã™Â†Ã˜Â³Ã˜Â¨, Ã˜Â¹Ã˜Â¨Ã˜Â¯Ã˜Â§Ã™Â„Ã˜Â¬Ã˜Â¨Ã˜Â§Ã˜Â±; Ã™Â†Ã˜Â¸Ã˜Â±Ã™Â¾Ã™ÂˆÃ˜Â±, Ã˜ÂÃ™Â…Ã˜Â²Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
When in doubt over duty and the absence of reason, it is the time for adhering to practical principle; but, there is disagreement among principalists as to what is the rimary rule in times of doubt. Some scholars including NÄÄ«nÄ« have accepted intellectual innocence as a primary rule, whereas others - especially ShahÄ«d Sadr -believe in intellectual precaution. NÄÄ«nÄ« refers to the rule âthe indecency of punishment before expressionâ in order to seek proof for his view. He considers the dependence of mobility upon the receipt of assignment as one of the kinds of evidence that can be referred to in order to prove intellectual innocence based on the rule of âthe indecency of punishment before expressionâ. He believes that punishment for the abandonment of mobility where there had been no cause for mobility will be condemned. On the contrary, ShahÄ«d Sadr criticizes and rejects the idea of NÄÄ«nÄ« and seeks to prove his own idea in light of âthe right of worshipâ theory. The present study conducted in a descriptive analytical manner aims at explaining both views, examining their evidences and arguments, and mentioning the foundations of the âthe right of worshipâ theory. Thus, the validity of ShahÄ«d Sadrâs theory will be proved.